The effect of topical anti blister products on the risk of friction blister formation on the foot. Issue 3 (August 2016) - Hashmi, Farina; Kirkham, Suzanne; Nester, Christopher; Lam, Sharon
Abstract: Introduction: Foot blisters are a common injury, which can impact on activity and lead to infection. Increased skin surface hydration has been identified as a risk factor for blister formation, indicating that a reduction in hydration could reduce the risk of blister. Method: Thirty healthy adults were randomised into 3 groups, each receiving a preventative foot blister treatment (2Toms ® Blister Shield ® ; Flexitol ® Blistop and Boots Anti–Perspirant Foot Spray). Cycles of compression and shear loads where applied to heel skin using a mechanism driven by compressed air. Temperature changes were measured during load application using a thermal imaging camera (FLIR Systems Inc. and Therm CAM™ Quick Report). Near surface hydration of the skin was measured using a Corneometer ® (C & K, Germany). Results: There was no significant difference in the rate of temperature change of the skin between the three groups compared to not using products (p = 0.767, p = 0.767, p = 0.515) or when comparing each product (p = 0.551). There was a significant decrease in near surface skin hydration, compared to baseline, after the application of powder (−8.53 AU, p = 0.01). There was no significant difference in hydration after the application of film former and antiperspirant (−1.47 AU, p = 0.26; −1.00 AU, p = 0.80, respectively). Conclusion: With the application of external load we found no significant difference in the effect of the three products on temperature change. The powder product demonstrated an effect on reducing the risk of blister. It is postulated that powder may have a barrier effect. Graphical abstract: Highlights: A method for testing the effects of anti-blister agents is proposed. The powder agent provides a degree of protection from risk of blister. The response of the skin to external loads did not differ between the agents tested.